Rapid and visual detection of aflatoxin B1 in foodstuffs using aptamer/G-quadruplex DNAzyme probe with low background noise. (15th January 2019) - Wang, Lumin; Zhu, Fawei; Chen, Miao; Zhu, YuQiu; Xiao, Jianbo; Yang, Hua; Chen, Xiaoqing
Highlights: A label-free aptasensor was developed for sensitive and rapid detection of aflatoxin B1 with low-background. Aptamers were used to immobilize two split G-rich sequence and control the formation of aptamer/G-quadruplex DNAzyme probe. To lower the background signal, Fe3 O4 @oMWCNTs were applied to facilely and effectively remove excess hemin for the first time. The proposed method can be readily applied for visual detection of aflatoxin B1 and aflatoxin M1. Abstract: Contamination of foods by aflatoxin B1 (AFB1) is a common serious problem. To improve the efficiency of AFB1 detection, this study aims to develop a sensitive aptasensor for detection of AFB1 in food samples based on the catalytic effect of aptamer/G-quadruplex DNAzyme probe. The resulting reassembly of this probe in the presence of hemin and K + catalyzes the generation of fluorescent 2, 3-diaminophenazine (DAP) from o -phenylenediamine (OPD). Interestingly, we first found that the high background induced by the superfluous hemin can be effectively suppressed with the aid of sequential adsorption and magnetic separation by magnetic oxidized multiwall carbon nanotubes (Fe3 O4 @oMWCNTs). This aptasensor exhibits a high sensitivity toward AFB1 with a detection limit of 0.02 ng/mL. The assay also shows higher selectivity for AFB1 compared to other reported agents and can be employed to detect AFB1 in foodstuffs, which might find broad practical applications in other food contaminants determination.